(untitled) (African Journal of Biomedical Research, 2021)
Painful diabetic peripheral neuropathy (DPN) is prevalent amidst diabetic patients. It develops with a background of long-standing hyperglycaemia, metabolic derangements and oxidative stress. Vitamin C an aqueous phase antioxidant which may help in combating oxidative stress. Vitamin C depletion occurs in diabetes and this has been reported to be associated with spinal and musculoskeletal pain. Therefore, this study was conducted to investigate the effect of vitamin C administration on neuropathic pain and peripheral nerve in DPN. Thirty wistar rats (180-200g) were grouped (n=10) into control (C), diabetic and vitamin C treated diabetic. Diabetic neuropathy was induced using 20% fructose and 150mg/kg.ip alloxan. Vitamin C (1g/kg.p.o) treatment via oral-canula lasted for two weeks. Neuropathy was assessed using tail flick and formalin paw lick tests. Peripheral nerve histology and sympathetic activity were assessed using light microscopy and tyrosine hydroxylase (TH) immunohistochemistry respectively. Oxidative and nitrosative stress markers (SOD, MDA, GSH, VC & NO) were evaluated using spectrophotometry. Hyperalgesia, paw numbness, sciatic nerve degeneration and reduced sympathetic activity were observed in diabetic rats showing peripheral neuropathy. However, these were reversed in vitamin C treated diabetic rats via mechanism related to upregulation of tyrosine hydroxylase activities and downregulation of oxidative and nitrosative stress, as SOD, NO and MDA were significantly (p<0.01) reduced, while GSH, VC and TH were increased (p<0.05) in Vitamin C treated rats. Thus, vitamin C may be an effective adjunct therapy for neuropathic pain relief, restoration of normal sensation in lower limbs and amelioration of diabetic peripheral neuropathy.